Robin Hood - Gilbert, Henry, 1868-1937; Crane, Walter, 1845-1915 (Hertfordshire : Wordsworth Classics, 1994)
Recounts the legend of Robin Hood, who plundered the king's purse and poached his deer and whose generosity endeared him to the poor.
Keywords: Robin Hood -- (Legendary character) -- Legends; Robin Hood -- (Legendary character) -- Legends; Folklore -- England